(untitled) (Eurasian Journal of Research, Development and Innovation, 2025)
This article examines the importance of engineering competitions and quizzes in developing research activities among students of technical universities. By integrating innovative teaching technologies such as practical projects and experiential learning, students have the opportunity to improve their problem-solving, critical thinking skills, and practical knowledge. The article highlights the benefits of engaging students in extracurricular activities that develop research-oriented thinking, ultimately contributing to a well-rounded education in engineering